PENGARUH DISIPLIN KERJA, REWARD DAN PENGALAMAN KERJA TERHADAP PENGEMBANGAN KARIER PEGAWAI BIRO PERENCANAAN & ADMINISTRASI (RENMIN) LEMDIKLAT POLRI - Karlina Triasafitriani (2021)
This research is a quantitative that aims to determine the influence of work discipline, reward and work experience on career development at Planning & Administrations Departemen at Police Education and Training Institutions. The research used a sample size of 99 respondents who were all police amployees at Planning & Administrations Departemen at Police Education and Training Institutions. The analytical technique used in this research is the Coefficient of Determination Test (R2) and T Test (Partial) using Smart PLS 3.0 software. The results of the test are (1) work discipline has a positive and significant effect on employee career development of Planning & Administrations Departemen at Police Education and Training Institutions (2) reward has a positive and significant effect on employee career development of Biro Planning & Administrations Departemen at Police Education and Training Institutions (3) work experience has a positive and significant effect on employee career development of Planning & Administrations Departemen at Police Education and Training Institutions. With an R2 value of 75.9%, it means that it shows the contribution of the variables of work discipline, reward and work experience on career development of the Planning & Administrations Departemen at Police Education and Training Institutions.